Património Urbanístico e Planeamento da Salvaguarda - Adelino Gonçalves (Olhares, 2018)
Urban heritage took four hundred years to establish itself as a cultural asset to be safeguarded and evolved along an historicalsocial process, rooted in the idea that urban sets and monumental architecture are part of the same category of historical values. In the second half of the nineteenth century, the notion of heritage stretched up and reached an urban dimension, but its social and political understanding did not release itself from theories and practices of intervention and safeguard action established within the architectural dimension from which came from. Aiming to contain change, they continue to resist to accept that change it is part of the nature of cities and to integrate it into the very meaning of the urban dimension of heritage. After all, of what do we talk about when we talk about urban heritage? Arising from various stimuli, this question guided the texts gathered here. They were written with different disciplinary perspectives because the measure that differentiates the urban dimension of heritage and architectural dimension is not metric or geometric. It is ontological and can only be understood in an integrated manner. In development, of course.